Penerapan Pembelajaran Tari Berbasis Online Learning - Nasya Saskia Aldila (Program Studi Pendidikan Tari FBS UNJ, 2021)
The purpose of this study is to investigate the learning process of Sirih Kuning dance to the XUPW students in SMK N 27 Jakarta as well as to describe the results obtained after learning Sirih Kuning dance online. The research method is descriptive qualitative with data collection techniques in the form of interviews, observation, literature study, and document study. Data analysis techniques used Miles and Huberman in the form of data reduction, data presentation, and conclusions. The data validity technique used triangulation technique by checking and matching the data that had been obtained from the interview with the observed data. The results of this study showed that online learning-based dance learning could run smoothly if it used the right platform. Students looked more active and enthusiastic during dance lessons using the zoom and whatsapp platforms. The use of this platform helped students establish interactions during learning activities. The demonstration method helped students to better understood the material being taught, while the drill method helped students to be more independent in absorbing the material by means of practice.